Succession Planning, Employee Retention and Organisational Effectiveness among Some Selected Organisations in Ghana. - Tetteh, J. (University of Ghana, 2015)
The study examined the relationship between succession planning, employee retention and organisational effectiveness among some selected organisations in Ghana. It further examined the effect of career development program on the relationship between succession planning and employee retention and also on the relationship between succession planning and organisational effectiveness. One hundred and eighty-eight (188) respondents were conveniently sampled from four organisations; two from the private and two from the public sector in the Greater Accra Region of Ghana. Using a quantitative design, all selected participants completed questionnaires on Succession Planning, Employee Retention, Organisational Effectiveness and Career Development Program. The Multiple Analysis of Variance and Hierarchical Multiple Regression were conducted on the data. The results indicated that, succession planning significantly predicted employee retention and organisational effectiveness. The result further indicated that, career development program significantly moderated the relationship between succession planning and employee retention. Career development program also significantly moderated the relationship between succession planning and organisational effectiveness. Based on the research findings, theoretical and practical implications are discussed as well as limitations and suggestions for future research also highlighted.
Thesis (MPhil.) - University of Ghana, 2015